Extrinsic and intrinsic motivation on work engagement in the hospitality industry: Test of motivation crowding theory. (April 2017) - Putra, Eka Diraksa; Cho, Seonghee; Liu, Juan
The aim of this study was to examine extrinsic and intrinsic motivations as the antecedents of work engagement and to empirically test the motivation crowding theory using hospitality employees. The findings showed that intrinsic motivation played an important role in improving employees' work engagement. The study also found that there was no indication that employees' intrinsic motivation diminished when extrinsic motivation entered. It is also suggested that employers need to understand that creating a comfortable workplace environment and making jobs more interesting and meaningful will increase employees' intrinsic motivation, which will help employees to engage more at work. Motivational antecedents of work engagement have been rarely studied and no studies have been conducted to research impacts of extrinsic and intrinsic motivators on employees' work engagement in the hospitality industry, particularly in small restaurant businesses. In addition, empirical studies on motivation crowding theory are needed due to the inconclusive results.